Impact of Revitalization of Social Cultural Changes in Culture: (Case Study in Serang Village Kasemen Banten) - Sampurna, Bayu; Hufad, Achmad; Komariah, Siti (International Conference on Elementary Education, 2020)
Banten Province, located in the western part of the island of has a region with very historical value. high, the old Banten area. Now the condition of the Banten Region has been untouched for a long time and has been left for years. The development of the old Banten Region is increasingly making the meaning of the region fade and making the object of the old historical Banten area sink. Banten Provincial Government in 2018 in collaboration with the City and Serang District governments finally began implementing a revitalization program with the aim of restoring the glory of old Banten, and increasing the number of visitors to the old Banten region. However, the phenomenon that occurred regarding the revitalization of the old Banten area turned out to have an impact on changes in the socio-cultural community around the old Banten Cultural Heritage area, namely in the Village of Kasemen Serang. The purpose of this research is to find out the picture of social and cultural changes in the people of Banten Kasemen Serang Village. In this study, researchers used a case study method with a qualitative approach, interviews were conducted on the main informants namely the Banten Provincial Tourism Office, the Public Housing Agency and the Banten Province residential area, the community and tourists based on these interviews obtained results and the conclusion that the community's mentality was not ready to accept innovations. carried out by the government, the community considers revitalization carried out as not having an upward impact on them